Pengaruh Nepotisme terhadap Kepuasan Kerja, Komitmen Organisasional dan Intention to Stay - Putra, Made Surya (Jurnal Aplikasi Manajemen, 2012)
One important issue in the social interaction in organizations is a matter of nepotism because workers'perceptions of nepotism affect job satisfaction, organizational commitment and intention to stay. The purpose of this study was to test and develop theoretical models of nepotism in relation to intention to stay within the framework of Equity Theory and Organizational Justice. Simple random sampling was using to choose respondent and data was analysis using Partial Least Square (PLS). Empirical data proving that nepotism should be measured by indicators from the perspective of reflexive ethical and not just by looking at family relationships/kinship. Hotel Melati managers are advised to use a Familiar management style and recruit workers from the local environment to increase endurance (survival) of hotels in the neighborhood. The model needs to be examined on organizations with different characteristics and are advised to include other variables as a mediating or moderator variable.